PENGARUH KUALITAS LAYANAN DAN LOKASI TERHADAP KEPUASAN PENGUNJUNG MUSEUM FATAHILLAH - Rieka Rahardjo; Sinthon L Siahaan (Panorama Nusantara, 2017)
This research aims to know the influnce of the quaility of service and location toward the satisfaction of visitors of the Museum Fatahillah both partially and simultaneously. The population in this study are Fatahillah Museum visitors. Sampling research use the technique of accidental sampling approach with 100 people. Independent variables in the research are service quality (X1) and location (X2),while dependent variable (Y) is the satisfaction of visitor. Data collection method using question form. Data analysis using multiple linier regression and analysis using SPSS program. Conclusion of this research is that quality of service and location influence on visitor satisfaction both partially and simultaneously.